MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR NEGERI LAWANG GINTUNG 2 KOTA BOGOR PADA TEMA WIRAUSAHA DENGAN MEDIA POWERPOINT - Rahmayanti . (Universitas Pakuan, 2020)
INCREASING STUDENT ACTIVITIES AND LEARNING OUTCOMES ON ENTREPRENEURIAL THEMES WITH POWERPOINT MEDIA AT LAWANG GINTUNG 2 ELEMENTARY SCHOOL, BOGOR CITYThis study aims to determine the increase in student activity and learning outcomes, describe the process of increasing student activity and learning outcomes, and measure the magnitude of the increase in activity and learning outcomes on entrepreneurial themes with the use of powerpoint media in class VI SD Negeri Lawang Gintung 2, Bogor City in the academic year 2019 / 2020. This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The results of this study indicate that using powerpoint media on the entrepreneurial theme can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using Powerpoint media in the learning theme of Entrepreneurship, the learning outcomes of students only reached an average value of 64.46 then an increase occurred after using Powerpoint media to 78.39 in cycle 1 and 94.78 in cycle 2. The results of the study in the final cycle showed that there were 97.45% of participants have completed their learning outcomes. So it can be concluded that the use of powerpoint media on entrepreneurial themes is very popular with students and there is an increase in student learning outcomes. Therefore, researchers suggest that the use of powerpoint media on entrepreneurial themes be socialized and used as an alternative in schools.